Effect of heat and filter sterilization on the efficiency of coleus aromaticus as an antibacterial agent against diabetic wound pathogens - Muniandy K.; Hassan Z.; Mohd Hafez Mohd Isa (International Journal of Pharmacy and Pharmaceutical Science, 2024)
Indexed by Scopus